Afro-global Management Innovation Practices: Re-imagining Work and Workplaces - Ungerer, Marius; by, with contributions (African Sun Media, 2021)
This book represents views, frameworks and practices on stimulating and realising our optimal potential as human beings in the context of a workplace where there is a desire to achieve shared goals and aspirations in order to accomplish positive economic, societal and environmental impacts and outcomes. It describes a vision of how life and work in organisations could be. We describe a new kind of organisation. Being a good person and doing good things while making profit are a real possibility for those management innovators who think beyond immediate trade-offs. In this book we explore management innovation as core study field and arena for re-inventing and re-imagining how people in organisations could execute management activities such as planning, organising, leading and controlling for multiple stakeholder satisfaction and benefits. Work can be much more joyful and fulfilling than we think, but it requires courage from us to take responsibility when freedom is offered.